Analisis Faktor-Faktor Produktivitas Usaha Tambak Udang L.Vannamei: Studi Kasus pada Desa Bumi Pratama Mandira, Kecamatan Sungai Menang, Sumatera Selatan - Priyambodo, Raka Respati; Luxianto, Rizky (UI Scholars Hub, 2020)
The large economic potential of Indonesian aquaculture industry, especially in L.vannamei species, shows how vital it is to decide the correct aquaculture methods to maximize productivity. Bumi Pratama Mandira Village in Sungai Menang Region, South Sumatra is an area whose main economic activity comes from shrimp farming activity and mostly cultivating L.vannamei. The village located in one of the most remote regions in South Sumatra, limiting farmer access and present them with unique conditions for shrimp farming. This uniqueness raising the urgency to select the correct methods to sustain the entire village economic conditions. This study will evaluate three cultivation methods (Extensive, Extensive Plus and Semi Intensive) which are commonly used by shrimp farmers in the area. Evaluation is done by com- paring variables which is consisted of production/m2, income m2 and profit/m2 from each of the cultivation methods using the student’s or welch t-test. The results of the t-test indicate that although there are signifi- cant differences for production/m2 and income/m2, there is no difference for the profit/m2. Meanwhile, the regression test showed a significant positive and linear relationship between the variables of feed usage, drug usage and the frequency of water mill use to the level of productivity, and the quadratic relationship between the level of stocking density with the level of productivity with the optimum point of stocking den- sity at 25PL / m2.